(untitled) (The Review of Diabetic Studies, 2024)
In the present times, blood type examination and detection is considered as one of the most important and crucial dimension; utilized in different clinical and medical settings. This may include therapy for cancer, obstetric emergencies, surgical procedures, trauma resuscitation, and blood disorders. Correctly identifying the patient’s and donor’s blood groups using the ABO and Rhesus (Rh) systems of blood groups and looking at the need of rapid results and precision level, nano-technology is considered as the most definite avenue. This study is follows cross-sectional study and will explore the knowledge and attitudes of healthcare professionals about this innovative technology and their perceived barriers and facilitators to the adoption of this technology in practice. The findings will inform policymakers and researchers about data that will support the translation of academic innovation to clinical practice in Jeddah, Saudi Arabia.